Does Influencer Credibility Directly Drive Purchases? Evidence from Indonesian Social Commerce Users - Anthony Kurniawan; Christian Setiawan; Fredric Wijaya; Anthonius Sogodoran Hutabarat (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This paper discusses the effects of credibility of influencer and sales promotions on consumers' purchasing decisions within social commerce, particularly in the Indonesian market. It further analyzes how purchase intention mediates, offering guidance for optimizing marketing tactics in this expanding digital landscape. A quantitative approach was utilized through an empirical survey involving 150 active social commerce users to perform the research. The survey held across the Indonesian cities of Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). Partial least squares structural equation modeling (PLS-SEM) and principal component analysis (PCA) were applied using SmartPLS software for structural model analysis and measurement. This paper reveals that both sales promotions and influencer credibility significantly enhance customers' purchase intentions, which subsequently drive their purchase decisions in social commerce. Sales promotions directly affect purchasing, while influencer credibility primarily boosts purchase intentions that indirectly lead to buying actions. This highlights the value of credible influencers and targeted promotions in increasing consumer engagement and conversions. This paper combined an analysis of influencer credibility and sales promotions on purchase decisions within social commerce, specifically in the Indonesian market. Unlike prior studies that examine these factors individually, this research integrates both elements with purchase intention as a mediating factor. This approach provides a more enhanced model for understanding consumer behavior in a social commerce environment.